The effects of modifying elements of written informed consent forms for elective surgical or invasive procedures: A systematic review. (February 2023) - Bühn, Stefanie; Huppertz, Elena; Weise, Alina; Lühnen, Julia; Steckelberg, Anke; Büchter, Roland Brian; Hess, Simone; Choi, Kyung-Eun (Anna); Mathes, Tim
Abstract: Objective: To study the effect of modifying content and design elements within written informed-consent-forms (ICF) for patients undergoing elective surgical or invasive procedures. Methods: We included (quasi-)randomized trials in which a modified written ICF (e.g. visual aids) was compared to a standard written ICF. We searched PubMed, Web-of-Science and PsycINFO until 08/2021. Risk of Bias was assessed. The complexity of intervention was assessed using the Intervention Complexity Assessment Tool for Systematic Reviews. Results: Eleven trials with 1091 participants were eligible. Effect sizes and levels of evidence varied from trivial to moderate andthere were contradictory findings for some outcomes. Providing patients with more informationin general or specific information on risks and complications mostly increased anxiety. The use of verbal risk presentation decreased anxiety and increased satisfaction.A lower readability level decreased anxiety and improved comprehension and knowledge. Conclusion: Our results suggest that providing more information and addressing certain types of risks have differential effects. While more information improved knowledge, it also increased anxiety. We did not find any or only insufficient evidence for many other possible ICF modifications. Practice implications: When developing ICFs the differential impact of different elements on patient important outcomes should be carefully considered. Highlights: We assessed the effect of elements of written informed consent forms (ICFs) using methods for SRs of complex interventions. Modifying written ICFs has differential effects, e.g. more information can increase anxiety but improve knowledge. Our results suggest that different elements have to be balanced in the development of written informed consent forms. Further research on the effects of specific ICF components and combinations is needed.